Asymmetry in the dynamic conditional correlation of gold returns and stock returns - Sinsukthavorn,Kittiporn; Alfredsson,Haukur (2014)
The purpose of this thesis is to explore the possibility of asymmetry in the dynamic conditional correlation of stock returns and gold returns. We hypothesize that this asymmetry might be different for large and small firms, as a result of size specific characteristics that may influence firm profitability and risk following negative market shocks. We investigate this on three different sized U.S. stock indices during a twenty two year long period by using the dynamic conditional correlation model and the asymmetric generalized dynamic conditional correlation model. Our results show that there is asymmetry in the dynamic conditional correlation of these stock indices and gold. Furthermore, we find that the asymmetric effect is not the same for large and small firms.
Keywords: DCC; AG-DCC; dynamic conditional correlation; asymmetry; gold; mid-cap; small-cap; size